Unconventional Magnetization Processes and Thermal Runaway in Spin-Ice Dy₂Ti₂O₇ - Slobinsky, D. (2010)
We investigate the nonequilibrium behavior of the spin-ice Dy₂Ti₂O₇ by studying its magnetization as a function of the field sweep rate. Below the enigmatic ''freezing'' temperature Tequil ≈ 600 mK, we find that even the slowest sweeps fail to yield the equilibrium magnetization curve and instead give an initially much flatter curve. For higher sweep rates, the magnetization develops sharp steps accompanied by similarly sharp peaks in the temperature of the sample. We ascribe the former behavior to the energy barriers encountered in the magnetization process, which proceeds via flipping of spins on filaments traced out by the field-driven motion of the gapped, long-range interacting magnetic monopole excitations. The peaks in temperature result from the released Zeeman energy not being carried away efficiently; the resulting heating triggers a chain reaction.